Shapers of urban form explorations in morphological agency - Larkham, P. J. (Peter J.) 1960-; Lilley, Keith D. (Routledge, 2014)
"People have designed cities long before there were urban designers. In Shapers of Urban Form, Peter Larkham and Michael Conzen have commissioned new scholarship on the forces, people, and institutions that have shaped cities from the Middle Ages to the present day. Larkham and Conzen collect new essays in "urban morphology," the people-centered predecessor to contemporary theories of top-down urban design. Shapers of Urban Form focuses on the social processes that create patterns of urban forms in four discrete periods: Pre-modern, early modern, industrial-era and postmodern development. Featuring studies of English, American, Western and Eastern European, and New Zealand urban history and urban form, this collection is invaluable to scholars of urban design and town planning, as well as urban and economic historians"-- Provided by publisher.